Angel financing in Asia Pacific : a guidebook for investors and entrepreneurs - Lo, John Y.; Mooney, Patrick; Wu, Po Chi (Emerald Group Publishing Limited, 2016)
Angel investment and finance have been spreading from Silicon Valley to other parts of the world, including Asia, at an accelerating pace. Yet there have been few attempts to document this phenomenon and examine the hows and whys of startup financing in the region. Angel Financing in Asia Pacific addresses this knowledge gap by approaching the subject matter from two angles. First, from a journalistic angle, it aims to capture the current status and recent developments in a number of countries or territories in Asia. In each country report, the respective author(s) trace the background, trends, and future outlook of technology and innovation driven developments and related angel investment activities. The second part of the book takes a more analytical and prescriptive angle to the subject; making recommendations, providing analysis, and suggesting new approaches to startup financing in the Asia Pacific region.